The Effect of Crude Protein Level in Diets on Serum Biochemical Indexes and Intestinal Microflora of Yellow Quails - Li, Y.X.; Zhang, Y.F.; Wang, Y.Q.; Pang, Y.Z.; Qi , Y.X. (International Journal of Poultry Science, 2011)
A study was carried out to determine the effect of crude protein level in diets on Serum Biochemical Indexes and Gastrointestinal Micro flora of yellow quails. Four diets with different crude protein levels 17.75%, 19.95%, 21.85%, 24.08% were used to feed 192 yellow quails during 50-day-old to 95-day-old in this experiment. The quails were randomly assigned to 4 groups by similar body weight, each of which was subdivided into 4 replicates of 12 quails each. At 95-day-old, two quails per replicates were selected randomly and slaughtered to collect the blood the caecal contents. The blood sample was used to analysis serum biochemical. The caecal contents was detected the colibacillus, lactobacillus and bifidobacterium. The results showed that ALT of diet 1 was significant low (p0.05). Serum TP of treatment 3 is high than treatment 1 (p0.05). The colibacillus and bifidobacterium were decreased and lactobacillus increased with the increased in dietary protein though there were no significant difference (p>0.05). These results indicated that the different level of dietary protein could not effect on gastrointestinal microflora significantly but significantly effect on serum biochemical indexes of yellow quails.